PERAN FORUM KOMUNITAS PEMUDA DALAM MENJAGA KEARIFAN LOKAL MASYARAKAT DESA TEGALGUBUG LOR - Ripa'i, Irpan; Nurizzati, Yeti; Mulyana, Asep (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2025)
This research discusses the strategic role of the Youth Community Forum in maintaining the local wisdom of the Tegalgubug Lor Village community, Cirebon Regency. The village has cultural traditions such as Baritan, the spirit of mutual cooperation, and religious values. However, the influence of globalization and modern lifestyles has caused the younger generation to move away from local values, raising concerns about the loss of cultural identity of the village community. The purpose of this study is to describe the activities of the youth community forum, identify the forms of local wisdom that are still maintained, and explain the forum's role in cultural preservation. The forum is expected to be an agent of change as well as a preserver of ancestral heritage. Youth community forums act as a link between tradition and the younger generation. Their activities strengthen cultural values and educate the community about the importance of local wisdom. Through social, cultural and educational activities, the forum strengthens the community's solidarity and collective identity. This research used a descriptive qualitative approach with in-depth interview techniques, observation, and documentation studies. Informants consisted of community leaders, forum administrators, and active youth. The analysis used the Miles and Huberman model. The results show that the forum organizes activities such as art festivals, traditional dance training, and information technology workshops. The forum also maintains the traditions of earth alms, magap sri, baritan, and tambourine art. The forum plays an active role in increasing community participation, maintaining the existence of local culture. Keywords: Community Forum, Local Wisdom, Youth.